Analysis of the impact of surface layer properties on evaporation from porous systems using column experiments and modified definition of characteristic length. Issue 5 (20th May 2014) - Assouline, Shmuel; Narkis, Kfir; Gherabli, Rivka; Lefort, Philippe; Prat, Marc
Abstract The hydraulic properties of the layer at the vicinity of the soil surface have significant impact on evaporation and could be harnessed to reduce water losses. The effect of the properties of the upper layer on the evolution of phase distribution during the evaporation process is first illustrated from three‐dimensional pore network simulations. This effect is then studied from experiments carried out on soil columns under laboratory conditions. Comparisons between homogeneous columns packed with coarse (sand) and fine (sandy loam) materials and heterogeneous columns packed with layers of fine overlying coarse material and coarse overlying fine material of different thicknesses are performed to assess the impact of upper layer properties on evaporation. Experiments are analyzed using the classical approach based on the numerical solution of Richards equation and semianalytical theoretical predictions. The theoretical analysis is based on the clear distinction between two drying regimes, namely, the capillary regime and the gravity‐capillary regime, which are the prevailing regimes in our experiments. Simple relationships enabling to estimate the duration of stage 1 evaporation (S1) for both regimes are proposed. In particular, this led to defining the characteristic length for the gravity‐capillary regime from the consideration of viscous effects at low water content differently from available expressions. The duration of S1, during which most of the water losses occur, for both the homogeneous and two‐layer columns is presented and discussed. Finally, the impact of liquid films and its consequences on the soil hydraulic conductivity function are briefly discussed.